The Global HIV Epidemics among Men Who Have Sex with Men (MSM). - Group, World Bank (Directions in Development., 2011)
This report explores the emerging epidemics of HIV among men who have sex with men (MSM) in low and middle income countries (LMIC). A case study approach is used to explore these epidemics in detail in Peru, Ukraine, Kenya, and Thailand. Systematic reviews of epidemiology and prevention science were used to understand these epidemics, and to assess the evidence for interventions in prevention, access to care and treatment, and human rights protections. The Goals model was then used to assess the potential impact at country level of responding to epidemics among MSM. Benefits were seen for over.